N-Terminal Ile-Orn- and Trp-Orn-Motif Repeats Enhance Membrane Interaction and Increase the Antimicrobial Activity of Apidaecins against Pseudomonas aeruginosa - Bluhm, Martina E. C.; Schneider, Viktoria A. F.; Schäfer, Ingo; Piantavigna, Stefania; Goldbach, Tina; Knappe, Daniel; Seibel, Peter; Martin, Lisandra L.; Veldhuizen, Edwin J. A.; Hoffmann, Ralf (Frontiers in Cell and Developmental Biology, 2016)
The Gram-negative bacterium Pseudomonas aeruginosa is a life-threatening nosocomial pathogen due to its generally low susceptibility towards antibiotics. Furthermore, many strains have acquired resistance mechanisms requiring new antimicrobials with novel mechanisms to enhance treatment options. Proline-rich antimicrobial peptides, such as the apidaecin analog Api137, are highly efficient against various Enterobacteriaceae infections in mice, but less active against P. aeruginosa in vitro. Here, we extended our recent work by optimizing lead peptides Api755 (gu-OIORPVYOPRPRPPHPRL-OH; gu = N,N,N’,N’-tetramethylguanidino, O = L-ornithine) and Api760 (gu-OWORPVYOPRPRPPHPRL-OH) by incorporation of Ile-Orn- and Trp-Orn-motifs, respectively. Api795 (gu-O(IO)2RPVYOPRPRPPHPRL-OH) and Api794 (gu O(WO)3RPVYOPRPRPPHPRL-OH)were highly active against P. aeruginosa with minimal inhibitory concentrations of 8-16 µg/mL and 8-32 µg/mL against E. coli and K. pneumoniae. Assessed using a quartz crystal microbalance, these peptides inserted into a membrane layer and the surface activity increased gradually from Api137, over Api795, to Api794. This mode of action was confirmed by transmission electron microscopy indicating some membrane damage only at the high peptide concentrations. Api794 and Api795 were highly stable against serum proteases (half-life times > 5 h) and non-hemolytic to human erythrocytes at peptide concentrations of 0.6 g/L. At this concentration, Api795 reduced the cell viability of HeLa cells only slightly, whereas the IC50 of Api794 was 0.23 ± 0.09 g/L. Confocal fluorescence microscopy revealed no colocalization of 5(6)-carboxyfluorescein-labeled Api794 or Api795 with the mitochondria, excluding interactions with the mitochondrial membrane. Interestingly, Api795 was localized in endosomes, whereas Api794 was present in endosomes and the cytosol. This was verified using flow cytometry showing a 50 % higher uptake of Api794 in HeLa cells compared with Api795. The uptake was reduced for both peptides by 50 % and 80 %, respectively, after inhibiting endocytotic uptake with dynasore. In summary, Api794 and Api795 were highly active against P. aeruginosa in vitro. Both peptides passed across the bacterial membrane efficiently, most likely then disturbing the ribosome assembly, and resulting in further intracellular damage. Api795 with its IOIO-motif, which was particularly active and only slightly toxic in vitro, appears to represent a promising third generation lead compound for the development of novel antibiotics against P. aeruginosa.